Analisis Determinasi Tingkat Net Core Operational Margin Pada Bank Umum Syariah di Indonesia - Komarudin Komarudin; Ayus Ahmad Yusuf (LPMP Imperium, 2019)
Purpose- The purpose of this study is to explore the impact of a bank’s internal and external factors on net core operating margin in Indonesia’s Islamic commercial bank's companies. Methods- A quantitative approach by using panel data regression with a period from 2nd quarter 2010 to 2nd quarter 2015. The object of this study is eight Islamic commercial banks companies which were listed in sharia bank directory of Central Bank of Indonesia and Financial Services Authority of the Republic of Indonesia, those selected by purposive sampling technique with specific criteria. Findings- This study can be concluded that capital adequacy ratio and average operational cost have a positive and significant impact on the net core operational margin. On the contrary, financing to deposit ratio, bank size, operational efficiency ratio, and BI rate have a negative and significant impact on net core operational margin. Research implications- The management needs to create an efficient banking system by reducing operational costs and improving management quality. Banks are also advised to increase the prudential principle in managing finance so that the risk of default can be minimized.